Do public subsidy schemes foster innovation and competitiveness in rnergy-intensive industries? - Heli Koski; Maria Wang (The Research Institute of the Finnish Economy (ETLA), 2024)
This study evaluates the impacts of public subsidies on firms in energy-intensive industries, focusing on R&D subsidies and compensation subsidies. Using firm-level data from Finnish energy-intensive industries between 2010 and 2022, it examines how these subsidies influence firm competitiveness and innovation outcomes. Compensation subsidies, designed to alleviate the additional electricity costs imposed by the EU Emissions Trading Scheme (ETS) on firms operating in certain energy-intensive industries, and to enhance their international competitiveness show no significant effects on employment, value added, or labor productivity. R&D subsidies, instead, demonstrate a substantial positive impact on innovation. Specifically, R&D subsidies significantly increase the citation stocks of climate change mitigation technology patents filed with the United States Patent and Trademark Office (USPTO). Total patent citation stocks associated with the European Patent Office (EPO) and USPTO also show statistically significant growth.
Keywords: D22; H23; L52; O3; Q58; 330; Firm subsidy; R&D subsidies; EU ETS; Competitiveness; Green innovation; Patents